DETEKSI DINI DIABETES MELLITUS GESTASIONAL - Novita Anggraini; Margareta Haiti (Jurnal Kesehatan dan Pembangunan, 2024)
The process of pregnancy is a physiological state experienced by a woman who will give birth to the next generation. During pregnancy a mother should carry out Ante Natal Care (ANC) at least 4 times which aims to keep the mother and fetus healthy and avoid and prevent complications or complications during pregnancy, childbirth, the period after delivery and the baby to be born. Gestational Diabetes Mellitus (DMG) is a disorder that can occur in pregnant women. DMG can have short and long term impacts on both the mother and the child. It is very important for pregnant women to check their blood sugar levels to detect GDM. The aim of this study was to find out some of the characteristics of pregnancy that are related to blood sugar levels of pregnant women. The method used in this study uses correlation analysis with a cross sectional approach. The population in this study were all pregnant women who checked their sugar on the posyandu service day at RB Sinta Km.16. Sampling using total sampling technique. The Kendal Tau test results obtained a p value of 0.361 more than 0.05, which means that there is no significant relationship between age and blood sugar levels in pregnant women and a p value of 0.256 more than 0.05 which means there is no significant relationship between parity and blood glucose levels. blood sugar in pregnant women. Suggestions for health workers to carry out counseling regularly so that pregnant women can maintain blood sugar levels and detect early so that gestational diabetes mellitus does not occur.